A study on the gasoline quality and performance - Chung, King Long. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The study of a comparison of gasoline quality by three local vehicle fuel suppliers namely SHELL Esso and Petronas are present in this report The objective of this report can be divided into three categories of analysis, which are post combustion emission level analysis, idling speed fuel consumption rate analysis and cold start-warm up duration analysis. The post combustion emission level analysis only limited to two type of post combustion of exhaust product namely carbon monoxide (CO) and hydrocarbon (HC). The exhaust product generated from gasoline consumption supplied by these three supplier has been analyst and experimental \vork also have been carry out to determine the percentage of carbon monoxide (CO) and hydrocarbon (HC) in part-per-million (ppm). The result from experimental work is use to make a comparison of fuel quality.